Penggunaan Teknologi dalam Dunia Pendidikan Tanpa Menghilangkan Nilai-Nilai Sosial - Silfiya Silfiya; Irwan Siagian (Journal on Education, 2024)
Advances in information technology are ushering in major transformations in various fields, including education. The teaching-learning process has been made easier by this technology. Excessive attachment to digital devices minimizes the opportunity for direct face-to-face interaction for the development of social and emotional skills. This research applies a qualitative descriptive method based on the constructivism paradigm, providing the researcher's subjective understanding of the phenomenon under study. Data were collected from articles to describe strategies to maintain social values in technology-based education. The results show that the use of technology in education, such as online learning, Augmented Reality (AR), and Artificial Intelligence (AI), accessibility is growing rapidly and has a significant positive impact on the quality of learning. Technology has shifted teaching methods from teacher-centered to student-centered, but it also makes it easier to cheat students and make them more interested in the virtual world than the real world. Student character is formed by various factors, namely heredity, and environmental factors. Environmental factors here include family environment, school environment, and positive school culture. Students' social values can be instilled through various activities at school, such as tolerance that helps them to build a harmonious school culture.